Stimulus Guru dan Respon Siswa dalam Pembelajaran Bahasa Arab Kelas X di SMKS Muhammadiyah Bungoro Kabupaten Pangkep - Sabilah Rahmi, Nur; Masnan, Sulaeman; Al-Mardhi, Radhi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Teacher Stimulus and Student Response in Class X Arabic Learning at SMKS Muhammadiyah Bungoro, Pangkep Regency. Supervised by Sulaeman Masnan and Muhammad Radhi Almardhi. This research uses a qualitative method that aims to find out how the form of teacher stimulus in learning Arabic class X SMKS Muhammadiyah Bungoro Pangkep Regency and how the form of student response in learning Arabic class X SMKS Muhammadiyah Bungoro Pangkep Regency. Data collection techniques in the form of observation, interviews and documentation. Technical data analysis includes data reduction, data presentation and conclusions. The sources of data in this study were Arabic teachers and students. The results of this study show that the Teacher Stimulus in Arabic language learning in class X, especially the RPL department at SMKS Muhammadiyah Bungoro Pangkep district, in general is not classified as good because the teacher is not an Arabic graduate, so he does not master the right methods, strategies, and evaluations in learning Arabic. However, the response of students is relatively good to the teacher’s stimulus in learning Arabic, that is, most students are happy and like to learn Arabic.Teacher Stimulus and Student Response in Class X Arabic Learning at SMKS Muhammadiyah Bungoro, Pangkep Regency. Supervised by Sulaeman Masnan and Muhammad Radhi Almardhi. This research uses a qualitative method that aims to find out how the form of teacher stimulus in learning Arabic class X SMKS Muhammadiyah Bungoro Pangkep Regency and how the form of student response in learning Arabic class X SMKS Muhammadiyah Bungoro Pangkep Regency. Data collection techniques in the form of observation, interviews and documentation. Technical data analysis includes data reduction, data presentation and conclusions. The sources of data in this study were Arabic teachers and students. The results of this study show that the Teacher Stimulus in Arabic language learning in class X, especially the RPL department at SMKS Muhammadiyah Bungoro Pangkep district, in general is not classified as good because the teacher is not an Arabic graduate, so he does not master the right methods, strategies, and evaluations in learning Arabic. However, the response of students is relatively good to the teacher’s stimulus in learning Arabic, that is, most students are happy and like to learn Arabic.Teacher Stimulus and Student Response in Class X Arabic Learning at SMKS Muhammadiyah Bungoro, Pangkep Regency. Supervised by Sulaeman Masnan and Muhammad Radhi Almardhi. This research uses a qualitative method that aims to find out how the form of teacher stimulus in learning Arabic class X SMKS Muhammadiyah Bungoro Pangkep Regency and how the form of student response in learning Arabic class X SMKS Muhammadiyah Bungoro Pangkep Regency. Data collection techniques in the form of observation, interviews and documentation. Technical data analysis includes data reduction, data presentation and conclusions. The sources of data in this study were Arabic teachers and students. The results of this study show that the Teacher Stimulus in Arabic language learning in class X, especially the RPL department at SMKS Muhammadiyah Bungoro Pangkep district, in general is not classified as good because the teacher is not an Arabic graduate, so he does not master the right methods, strategies, and evaluations in learning Arabic. However, the response of students is relatively good to the teacher’s stimulus in learning Arabic, that is, most students are happy and like to learn Arabic.